Pengaruh Akupresure (TITIK LI 4 dan SP 6) Terhadap Durasi Persalinan Kala I Fase Aktif - Yulianti, Indra; Prameswari, Veryudha Eka (Innovative: Journal Of Social Science Research, 2025)
One intervention that can help speed up the progress of labor is giving acupressure. Providing complementary therapy to birthing mothers is considered safer and has minimal side effects compared to invasive therapy. The acupressure method effectively reduces pain and strengthens contractions, prevents the transmission of harmful stimuli, increases the amount of endorphins in the blood and speeds up the process of labor. If the progress of labor is not handled properly, it can cause birth complications. The aim of the research was to determine the difference between the Li 4 and Sp 6 acupressure points on the duration of the first stage of labor. The research design uses a quantitative descriptive research type with a quasi-experimental design. The sample in this study was 45 respondents. The hypothesis used to test the difference between two means with the right-hand test is the t test if the data distribution is normal with a probability value ≥ 0.05 and if the data distribution is not normal with a probability value < 0.05 then use the Man Whitney test.The research results obtained, Output "Test Statistics" Asymp value. Sig. (2-tailed) is 0.000 < 0.05, so there is a significant influence between SP6 point acupressure on the duration of the first stage of labor in the active phase. Meanwhile, the output "Test Statistics" acupressure point LI4 with Asymp value. Sig. (2-tailed) is 0.000 < 0.05, so there is a significant influence between LI4 point acupressure on the duration of the first stage of labor in the active phase. The results of the research are that it is hoped that health workers can use the acupressure method at points SP6 and LI4 to speed up the duration of the 1st stage of labor. This method is included in the application of maternal care to speed up the labor process.